Genomic data-sharing: what will be our legacy? - Callier, Shawneequa; Husain, Rajah; Simpson, Rachel (Frontiers in Genetics, 2014)
Prior to 1974, the Tuskegee Syphilis experiments, expansive use of the HeLa cells, and other blatant instances of research abuse pervaded the medical research field. Discussion today about these challenges have caused the general public to develop a reluctance and distrust for medical research. This has significant implications for the advancement of genomic science, and the public's perception of genomic research.